STRENGTHENING THE QUALITY CONTROL CIRCLE MANAGEMENT BY BUILDING PARTNERSHIP PROGRAMS IN THE DIGITAL COMMUNITY ERA - Saleha, Latifatus (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Quality Control Circle management in an institution provides positive energy to an institution in building institutional quality control; strengthening control circle management is needed to continue to support institutions in improving their quality, especially in the era of digital society. This study aims to analyze and examine the direction of the Quality Control Circle through a partnership at RA Perwanida III Karanganyar Paiton Probolinggo. This study uses a qualitative approach. Technical analysis of data through interviews, observation and documentation is then carried out by reduction, which is processed on the last data display to conclude. Research shows gains; first, Quality Control Circle management has been running at RA Perwanida III. This management is carried out through planning, partnership programs, school branding and evaluation. The implications obtained for institutions are that the quality of institutions is increasing, as seen in institutions that are increasingly recognized by the wider community, with a marked increase in students from year to year.